Evaluation of four novel protein sources as alternatives to soybean meal for two specifications of cage-farmed grass carp (Ctenopharyngodon idellus) deeds: Effect on growth performance, flesh quality, and expressions of muscle-related genes - Fan, Ze; Li, Chenhui; Wu, Di; Li, Jinnan; Wang, Liansheng; Cao, Dingchen; Miao, Linghong; Xie, Shouqi (Frontiers in Marine Science, 2022)
Costs associated with the use of soybean as a food source in aquaculture have imposed constraints on its use in this industry. Thus, research is now focusing on alternative sources of protein for use in aquaculture. Here, we assessed the effect of total replacement of soybean meal (SBM) by Clostridium autoethanogenum protein (CAP), Tenebrio molitor meal (TMM), cottonseed protein concentrate (CPC), and chlorella powder (CHP) in diets for small specimens (initial body weight: 239.72 ± 10.75 g) and large specimens (initial body weight: 638.32 ± 12.64 g) of grass carp. For that purpose, five isonitrogenous (300 g/kg) and isoaliphatic (58 g/kg) diets were formulated with SBM, CAP, TMM, CPC, and CHP as the only dietary protein source. Triplicate groups of fish were fed the experimental diets for 56 days. Results showed that irrespective of protein sources, large specimens of grass carp obtained the significantly reduced weight gain rate (WGR), specific growth rate, moisture, crude ash contents, drip loss rate, and gene expressions of muscle S6K, MyoD, and Myf-5, and the significantly increased crude protein and crude lipid contents, hardness, cohesiveness, adhesiveness, springiness, chewiness and shear force of muscles, and gene expressions of muscle TOR, 4EBP1, MyoG, MRF4, and MSTN-1. Regardless of size, the CHP group possessed markedly higher WGR, protein efficiency ratio, crude protein contents, hardness, adhesiveness, chewiness values, and gene expression levels of muscle TOR, 4EBP1, Myf-5, and MRF4, and significantly lower feed conversion rate, drip loss rate, and gene expressions of muscle S6K and MSTN-1. For small specimens or for large specimens, the essential amino acid contents of the CHP group were highest, and CHP markedly elevated the delicious amino acid and glycine contents in comparison with the SBM. Moreover, the CPC group also realized the function of promoting the growth and improving the flesh quality to a certain degree. However, total replacement of soybean meal by CAP and TMM in grass carp diets restrained the growth and damaged the flesh quality in varying degrees. Overall, comparatively, total replacement of SBM with CHP not only improved growth performance and feed use, but also enhanced the flavor and texture of the fish by improving the amino acid composition and water-holding capacity of muscle, as well as improving muscle growth by positively impacting the expression of genes associated with the regulation of growth and development. Therefore, CHP could be a potential protein source to replace SBM in diets for use in the aquaculture of grass carp.